Utilization of Whole-Cell MALDI-TOF Mass Spectrometry to Differentiate Burkholderia pseudomallei Wild-Type and Constructed Mutants. - Suthamat Niyompanich; Kitima Srisanga; Janthima Jaresitthikunchai; Sittiruk Roytrakul; Sumalee Tungpradabkul (PLoS ONE)
Whole-cell matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (whole-cell MALDI-TOF MS) has been widely adopted as a useful technology in the identification and typing of microorganisms. This study employed the whole-cell MALDI-TOF MS to identify and differentiate wild-type and mutants containing constructed single gene mutations of Burkholderia pseudomallei, a pathogenic bacterium causing melioidosis disease in both humans and animals. Candidate biomarkers for the B. pseudomallei mutants, including rpoS, ppk, and bpsI isolates, were determined. Taxon-specific and clinical isolate-specific biomarkers of B. pseudomallei were consistently found and conserved across all average mass spectra. Cluster analysis of MALDI spectra of all isolates exhibited separate distribution. A total of twelve potential mass peaks discriminating between wild-type and mutant isolates were identified using ClinProTools analysis. Two peaks (m/z 2721 and 2748 Da) were specific for the rpoS isolate, three (m/z 3150, 3378, and 7994 Da) for ppk, and seven (m/z 3420, 3520, 3587, 3688, 4623, 4708, and 5450 Da) for bpsI. Our findings demonstrated that the rapid, accurate, and reproducible mass profiling technology could have new implications in laboratory-based rapid differentiation of extensive libraries of genetically altered bacteria.